Modern IoT Onboarding Platforms for Advanced Applications A Practitioner's Guide to KIS.ME - Witczak, Marcin (Studies in Systems, Decision and Control, 2023)
This is an open access book. The book starts with an introductory IoT overview related to its selected scope of applications. There is no doubt that digitalization solutions from Industry 4.0 and the Internet of Things (IoT) can be perceived as excellent candidate strategies capable of handling the above-stated issues concerning measurements and transparency. However, IoT tools themselves can provide appropriate data only, while their efficient integration and application are possible using a dedicated onboarding platform only. To settle this issue, the book undertakes the problem of modern IoT onboarding platforms for the advanced applications pertaining to manufacturing and logistics. In particular, instead of deliberating about a possible hypothetic platforms, an existing and efficient one is employed, which is called KIS.ME. KIS.ME (Keep It Simple. Manage Everything) is a complete IoT solution for a simple integration in manufacturing and logistics. It is composed of a set of hardware devices (KIS.BOX, KIS.IO and KIS.LIGHT), which are intuitively integrated with the cloud platform called KIS.MANAGER. Moreover, the entire platform is an open one, and hence, it enables communication with external services using KIS.API architecture. The application range of KIS.ME is extensive. This is due to the intuitive implementation and visualization of a user-defined key performance indicators (KPIs), which constitute effective optimization measures. Thus, the potential areas of application of KIS.ME are, e.g., manufacturing, warehouse management and logistics. Indeed, triggering and/or ordering various tasks can be immediately and efficiently implemented with KIS.ME. Such an approach translates directly to the savings of the time and energy. Subsequently, a gradual introduction to KIS.ME platform is presented, which constitutes the base for further advanced applications including logistics, control and maintenance of various processes. Finally, the potential of KIS.API communication framework is utilized for an efficient communication with external services.